Pengaruh Kepatuhan Diet, Aktivitas Fisik dan Pengobatan dengan Perubahan Kadar Gula Darah pada Pasien Diabetes Mellitus Suku Rejang - Almaini Almaini; Hendri Heriyanto (JURNAL KEPERAWATAN RAFLESIA, 2019)
Diabetes mellitus (DM) is a chronic disease characterized by blood glucose levels exceeding normal and impaired metabolism of carbohydrates, fats and proteins due to a relative or absolute deficiency of insulin hormones. This study aimed to determine the relationship between dietary compliance, physical activity, and adherence to taking medication with blood sugar levels when in patients with type 2 diabetes mellitus. This type of research was analytical with a cross-specific approach that uses a sample of 46 Rejang tribal diabetes mellitus patients who come to Curup Health Center, Prumnas Health Center and Delima Village Health Center during the period of August to October 2018 which met the criteria for inclusion and exclusion. The instruments used were food recall forms, questionnaires, medical records and glucometers. The results of the study were processed by bivariate analysis using the chi square test and multivariate analysis with logistic regression test. The results of the bivariate statistical test dietary compliance variable p = 0.001 OR = 15,343, CI = 3,327-67,636, and the medication adherence variable p = 0,035, OR = 4,038, CI 1,061-15,370. There was a significant relationship between diet compliance, adherence to taking medication with blood sugar levels when in patients with diabetes melititus Rejang tribe Rejang Lebong District. DM patients are expected to always adhere to diet, physical activity and medication treatment.